Using a Debate method to Increase the Students’ Speaking Skill on Discussion Text at Class XII SMAN 1 Kota Bengkulu at the 1ST Semester Academic Year 2017/2018 - Laina Tusifah (Universitas Bengkulu, 2019)
This research is done because the mean of pretest speaking is 65.73. The KKM is 75.00. The problems of this research are: 1) Can the use of a Debate Method increase the students’ Speaking Skill on Discussion Text at class XII SMAN 1 Bengkulu?. 2) How is the effectiveness of procedures of Using a Debate Method to Increase the Students’Speaking skill on Discussion Text at class XII SMAN 1 Bengkulu? The aims of this research are: 1).To increase the students’ speaking skill on Discussion Text at class XII SMAN 1 Bengkulu. 2).To find out how the effective procedure of using a debate method to increase the students’ speaking skill on discussion text at class XII SMAN 1 Bengkulu. This classroom action research which uses descriptive qualitative technique. This method uses pre-test and two cycles. Each cycle consists of four steps: planning, action, observation, and reflection. The source of the data is the teacher, collaborator as observer and students, and the result of the test. The total of the students are 35 students. Technique and collecting data uses observation and test.The result of classroom action research from observation cycle 1 is not good, that is 65%. And the result speaking test cycle1 is not good either, the mean score is 74.93%. 2 students get score 55-64, and the percentage is 5.71%. 12 students get score 65-74, and the percentage is 34.29%. 21 students get score 75-84 and the percentage is 60%. N0ne get score 85-94. The result of observation cycle 2 is good, that is 89%, and so is the result speaking test cycle 2, and the mean score is 80,64% .None of students get score below 75, and the percentage means 0%, 31 students get score 75-84, and the percentage is 88,57%. 4students get score 85-94, and the percentage is 11.43%. And even thought none student gets score 95-100 ,but the result is satisfied. The mean is 80,64. From the observation result of the test cycle 2 shows that the success of the learning process is good. KKM for English is 75.00, so the learning activity of students is fulfilled for the KKM. From the result of the cycle test 2, the mean score is 80,64% , learning activity uses a Debate Method to Increase the students’ speaking skill on Discussion Text at class XII IPS 2 SMAN 1 Bengkulu semester 1 academic year 2017-2018 is successful.